Leading and managing the competence‐based curriculum: conscripts, volunteers and champions at work within the departmentalised environment of the secondary school. Issue 3 (1st September 2013) - Downey, Christopher; Byrne, Jenny; Souza, Ana
Abstract : This article presents a sub‐set of findings from a research project describing the experience of four case study schools which have implemented a competence‐based curriculum (CBC) for students in their first year of secondary education. Secondary schools are highly departmentalised environments with organisational structures based primarily around subject departments and this can present a considerable challenge to such a multidisciplinary curriculum initiative. School leaders and teachers involved in the implementation and development of a CBC speak in terms of championing and legitimising the curriculum to their subject specialist colleagues. Teachers recruited to the competence‐based approach were sometimes described as a mix of volunteers and conscripts and overcoming any initial scepticism toward the approach required the position and status of the curriculum initiative to be established within the departmentalised organisational structure of the secondary school, and required continuing advocacy for the competence‐based approach.